Inference from Weak Hadiths in Beliefs from Sunni Scholars: الاستدلال بالحديث الضعيف في العقائد عن علماء أهل السنة - Muhammad Esmail, Allaa Eddin (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
تعد العقيدة الإسلامية هي أهم علوم الشريعة فبها يدخل الإنسان للإسلام وإذا اختل ركن من أركان العقيدة يخرج الإنسان من الدين، ولذلك ذكر العلماء أن مصادر العقيدة يجب أن تكون ذات موثوقية عالية ولذلك كانت العقيدة الإسلامية مأخوذة من كتاب الله ومما تواتر وصح من قول النبي صلى الله عليه وسلم. وقد قرر علماء العقيدة أن الحديث الضعيف لا يؤخذ به في باب العقائد بل لا بد لتقرير أبواب الإيمان من أن يكون الحديث صحيحاً سالماً لا علة فيه. ولكن هذه القاعدة العامة قد لا يسير العلماء على وفقها في كل الأوقات حيث نجد أنهم في فروع العقيدة كانوا يتساهلون في الاستدلال ببعض الأحاديث الضعيفة. وتأتي الدراسة هنا لتبين مصادر العقيدة وتتحدث عن منهج السلف الصالح في الاستدلال بالحديث الضعيف، وعن ضوابط الأخذ بالحديث الضعيف في العقائد، ثم يذكر الباحث أمثلة من استدلالات العلماء بالحديث الضعيف في تقرير فروع العقيدة الإسلامية، والله الموفق للصواب والحمد لله رب العالمين. الكلمات المفتاحية: الحديث الصحيح، العقيدة، الحديث الضعيف، الملائكة، الدليل. Abstract The Islamic creed is the most important science of Sharia, through which a person embraces and follows Islam, and if one of the pillars of the creed is missing, then the person steps out of Islam. For this reason, the scholars mentioned that the sources of the creed must be highly authenticated and certified. Therefore, the formation and extraction of Islamic creed is based on al-Quran, and on authentically documented sayings of Prophet Muhammad, may Allah bless him and grant him peace. The creed science scholars and experts have declared that a doubtful and unreliable hadith is not to be taken into account in the science of creed; rather it is necessary to establish the science of creed and its sections that the hadith must be authenticated and attested without having any fault or weakness. However, scholars may not follow this general (but) important rule at all the times, as we find that in the subjects and chapters of creed they used to be lenient in deducing some doubtful and unreliable hadiths. The study comes here to explain the sources of science of creed and to discuss about the approach of the righteous predecessors in deduction and argumentation using doubtful and unreliable hadiths, and about the rules and regulations for adopting weak hadiths in the science of creed. Then the researcher mentions examples of scholars’ argumentation using the weak hadith in establishing the sections of the Islamic faith. And all praises to almighty Allah. Keywords: Hadith sahih, belief, weak hadith, angels, guide.